PENINGKATAAN KOMPETENSI GURU MELALUI PENGEMBANGAAAN MODUL PEMBELAJARAN BERDIFERENSIASI: STUDI KASUS DI SMP NEGERI I KEMANG : Increasing Teacher Competency Through Development Of Differentiated Learning Modules - Patras, Yuyun Elizabeth; Kurniani, Dini; Hidayat, Rais (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
This research aims to enhance teacher competency in developing differentiated learning modules at SMP Negeri I Kemang. The study used a school action research method, involving 28 subject teachers, with data collected through observations, questionnaires, and interviews. The collected data was processed and analyzed descriptively statistically to assess the teacher competence level in each research cycle. Findings revealed that some teachers had not prepared learning modules or followed the module flow. To address these issues, coaching, counseling, and mentoring were provided. Results showed an overall improvement in teacher performance, with notable competency increases from cycle I to cycle II. Despite this progress, some teachers still require further attention. The study highlights the need for ongoing support and supervision of differentiated teaching modules to enhance learning quality and student outcomes. The research demonstrates that improving teacher competency in module development positively impacts learning quality and student achievement. Continuous efforts and support are essential for sustained improvement. These findings can guide schools and stakeholders in enhancing educational quality.